MODEL DEVELOPMENT OF ORGANIZATIONAL READINESS IMPACT ON PROJECT DAN FINANCIAL PERFORMANCE FROM ORGANIZATIONAL CAPABILITY PERSPECTIVE - Fitria Gumilang, Zahwa
Due to Covid-19 pandemic, mobility restrictions were imposed which forced non- essential economic sectors to limit their operational activities. This is the main cause for the decline in financial performance. On the other hand, the pandemic has accelerated the adoption of digital technology in society, including in the company. Organizational readiness in embracing digital technology and transforming the business towards a digital-based business have become paramount for the survival of firms. One of them, PT. Dago Energi Nusantara which is a technical consulting company in the fields of oil, gas and geothermal. Currently, PT. Dago Energi Nusantara is preparing to integrate digital technology with its existing resources. However, PT. Dago Energi Nusantara is still experiencing financial pressure. One of the factors that are considered influential is the low capability of the organization. The company's ability to manage projects and seize opportunities for innovation and product/service diversification is still considered weak. This has a negative impact on project performance, which has the largest contribution to the company's financial performance. Therefore, this study aims to examine the relationship of the five factors including organizational readiness, dynamic capability, project management capability, project performance and financial performance. This study uses quantitative methods and using non-probability sampling with purposive sampling as data collection technique. There are 30 indicators used to measure 5 research constructs. A total of 85 data were collected from December 27th of 2021 to January 27th of 2022. The data were processed using the PLS-SEM method with the help of SmartPLS software. This study is expected to contribute to the literature by examining the relationship between factors including organizational readiness, organizational dynamic capability, project management capability, project performance and financial performance. Based on the results of the bibliometric analysis, there has been no previous research that describes the relationship between the five constructs in one empirical study. The results of this research indicate that organizational readiness had a positive effect on project performance through the mediating role of organizational capabilities, namely dynamic capabilities and project management capabilities. Dynamic capabilities and project management capabilities were found to have a positive effect on project performance. Project performance was also found to have a positive effect on financial performance. Meanwhile, there was no positive and significant effect of dynamic capability on project management capability.